Pentingnya Bermadzhab dan Larangan Fanatisme Menurut Pandangan KH. Hasyim Asyâ€™ari - Mohamad Zaenal Abidin (Permata : Jurnal Pendidikan Agama Islam, 2020)
K.H. Hasyim Ash'ari was a great scholar in the 19th century from Java. He was known not only as a cleric figure and founder of the largest organization in Indonesia and even in the world of NU (Nahdlotul Ulama), but more than that he was also known as a National Hero whose first President Ir Soekarno had established him as one of the national heroes that was worth remembering - one of the most famous services in building the independence of the Indonesian people is through his fatwa on the Resolution of Jihad. The important concept of bermadzhab in his view is the result of dialectical life in solving the multidimensional crisis problems experienced by Muslims especially in Indonesia-hejaz. Namely the existence of differentiation between religious groups, including schools in Islamic law. So this thought seeks to offer the concepts of diligence, doctrine and imitate. Thinking about the importance of adamab in his books "ahlis sunnah wal Jama'ah treatise" and "treatise fi taakkudi bi akhdzil madzahibil arba'ah", even though in the grouping of the stages of history is weak, but the thought is a genuine product of renewal of Islamic law from K.H. Hasyim Ash'ari, in a sociological perspective, can be categorized as an effort to purify Islamic teachings with the solution of rationalism in the schools and return to the khittoh of the salafus sholih scholars. Keyword : Mahzab; fanaticism; KH. Hasyim Asyâ€™ari Abstrak K.H. Hasyim Asyâ€™ari adalah seorang ulama besar di abad 19 dari jawa. Beliau dikenal tidak hanya sebagai seorang tokoh ulama dan pendiri organisasi terbesar diindonesia bahkan didunia NU (Nahdlotul Ulama), namun lebih dari itu beliau juga dikenal sebagai seorang Pahlawan Nasional yang mana Presiden pertama Ir Soekarno telah menetapkannya sebagai salah satu pahlawan nasional yang patut dikenang jasa-jasanya dalam membangun kemerdekaan bangsa Indonesia salah satunya yang paling masyhur adalah lewat fatwanya tentang Resolusi Jihad. Konsep pentingnya bermadzhab dalam pandangan beliau adalah hasil dialektika kehidupannya dalam menyelesaikan problematika krisis multidimensi yang dialami oeh umat islam khususnya di indonesia-hijaz. Yaitu adanya diferensiasi antar kelompok keagamaan, tak terkecuali madzhab-madzhab dalam hukum islam. Sehingga pemikiran ini berusaha memberikan tawaran-tawaran konsep berijtihad, bermadzhab dan bertaqlid. Pemikiran tentang pentingnya bermadzhab didalam kitabnya â€œrisalah ahlis sunnah wal jamaâ€™ahâ€ dan â€œrisalah fi taakkudi bi akhdzil madzahibil arbaâ€™ahâ€, walaupun dalam pengelompokan terhadap tahapan-tahapan sejarah lemah, tetapi pemikiran tersebut adalah produk genuine pembaruan hukum islam dari K.H. Hasyim asyâ€™ari yang dalam perspektif sosiologis dapat dikategorikan sebagai upaya pemurnian ajaran islam dengan solusi rasionalisme ber-madzhab dan kembali ke khittoh ulama salafus sholih. Kata kunci: Bermahzab; Fanatisme; KH. Hasyim Asyâ€™ari